Proceedings of the 17th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2009
DOI: 10.1145/1653771.1653812
|View full text |Cite
|
Sign up to set email alerts
|

On-line discovery of flock patterns in spatio-temporal data

Abstract: With the recent advancements and wide usage of location detection devices, large quantities of data are collected by GPS and cellular technologies in the form of trajectories. While most previous work on trajectory-based queries has concentrated on traditional range, nearest-neighbor and similarity queries, there is a increasing interest in queries that capture the "aggregate" behavior of trajectories as groups. Consider for example, finding groups of moving objects that move "together", i.e. within a predefin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 20 publications
0
112
0
11
Order By: Relevance
“…Vieira et al (2009) identified three groups of 'collective' patterns in moving object databases: clustering for moving objects, convoy queries and flock patterns. Moving clusters (Jensen et al 2007) and convoy queries (Jeung et al 2008) differ from flock patterns mainly because they do not necessarily contain the same objects during the lifetime of a cluster or convoy.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Vieira et al (2009) identified three groups of 'collective' patterns in moving object databases: clustering for moving objects, convoy queries and flock patterns. Moving clusters (Jensen et al 2007) and convoy queries (Jeung et al 2008) differ from flock patterns mainly because they do not necessarily contain the same objects during the lifetime of a cluster or convoy.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, Gudmundsson and van Kreveld (2006) have shown that the discovery of fixed flocks -defined as patterns where the same entities stay together during the entire interval -is an nondeterministic polynomial time-hard problem. Vieira et al (2009) were the first to present an exact solution for reporting flock patterns in polynomial time and also for those that can work effectively in real time. Their work revealed that a polynomial time solution can be found through identifying a discrete number of locations to place the centre of the flock disk.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…One area of related work includes a number of recent studies [20,21,22,23,24] that investigate similarity between objects' (e.g., people, cars) locations in time, represented as trajectories, for various reasons (e.g., to identify moving convoys, to recommend carpool partnerships). In particular, the similarity between trajectories can be used to infer social connections among people as shown by Li et al [3].…”
Section: Introductionmentioning
confidence: 99%